2019
DOI: 10.15294/kemas.v14i3.14570
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of PMTCT and MCHS Integration in Indonesia, Analysis by Integration Analysis Framework and CFIR

Abstract: Integration was strategy of PMTCT (Prevention of Mother to Child HIV Transmission) and MCHS (Mother and Child Health Services) since 2006. This systematic review explored integration level between PMTCT and MCHS. Literature searched from June 2015 to January 2016 through Google, Google Scholar, University Library Website, Portal Garuda, ProQuest, PubMed and 90 institutions in Jakarta. Keywords were PMTCT, HIV Mother, PPIA HIV Evaluation and HIV PMTCT Evaluation. We yielded 157 literatures from 1995-2015. Resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…This under-utilization of VCT by pregnant women occurs when respondents have been contacted by health workers, but the pregnant women ignore instructions from health workers and do not make VCT visits. Wiraharja, Trisnantoro, Mahendradhata, & Praptoharjo (2019) showed that integration has no direct impact on the results and is not a sole solution to the PMTCT issue. Influencing factors include resource factors, inclusion of patients' needs and perspectives in the service, network and communications factors, external policy and incentives, leadership engagement and access to knowledge and information.…”
Section: Table 2 Results Of Multivariate Analysis Of the Variables And Use Of Vct In Gianyar District In June 2019mentioning
confidence: 99%
“…This under-utilization of VCT by pregnant women occurs when respondents have been contacted by health workers, but the pregnant women ignore instructions from health workers and do not make VCT visits. Wiraharja, Trisnantoro, Mahendradhata, & Praptoharjo (2019) showed that integration has no direct impact on the results and is not a sole solution to the PMTCT issue. Influencing factors include resource factors, inclusion of patients' needs and perspectives in the service, network and communications factors, external policy and incentives, leadership engagement and access to knowledge and information.…”
Section: Table 2 Results Of Multivariate Analysis Of the Variables And Use Of Vct In Gianyar District In June 2019mentioning
confidence: 99%